Trade Credit and Bank Credit under asymmetric environment. The case of industrial enterprises of the Peruvian economy: 2000-2014 (Advances) - Cortez Cortez, Gaby (2015)
The sources of short-term financing of companies, such as trade credit and bank credit relationships, linkages or complementarities are part of the analysis in this study. Several studies and authors have emphasized in some of these funding sources and the reasons why companies turn to these sources. This study aims to demonstrate that all these hypotheses can be consolidated on an approach whereby trade credit and short term financial credit are united in the same process for the maintenance of the financial needs of companies in the process of movement of goods.